Підвищення завадозахищеності засобів радіозв’язку від навмисних завад - Єпішкін, С. О.; Цибульников, Д. І. (ХНУРЕ, 2019)
In the scientific work is carried out the analysis actual in modern time - time of military conflict, means of increasing the noise immunity of radio communication systems from unintentional interference. Description of the method of increasing the noise i mmunity and explanatory scheme of the proposed improvement method is given. Method is based on the use of radio communication with duplicate transmitters.
Keywords: ППРЧ; підвищення завадозахищеності